The Meaning of Paul’s Statement “To Live is Christ and to Die is Gain” and Its Implications for Believers - Situmorang, Alexander; Louisa, Elis; Gea, Siabdul; Sambur, Carol Sally (Proskuneo: Journal of Theology, 2025)
Philippians 1:21 expresses the Apostle Paul’s declaration that life is entirely for Christ, while death is gain because it leads to eternal fellowship with Him. This study explores the theological meaning of Paul’s statement “to live is Christ and to die is gain” and its implications for believers in contemporary life. The research applies a descriptive-qualitative method with a literature study approach, using the Epistle to the Philippians, Paul’s other letters, and relevant theological writings as primary sources. The theoretical framework is built on Paul’s understanding of life in Christ, the calling of believers, and the hope of eternal life. The findings reveal that living in Christ means making Him the center of faith, obedience, and service, while death is not to be feared but embraced as gain, since it opens the way to eternal communion with Christ. The study concludes that this understanding calls believers to live purposefully, remain steadfast in faith, and face suffering and challenges with strong hope in Christ. Ultimately, Paul’s statement is not merely a theological principle but a spiritual foundation that shapes Christian identity and mission: life becomes an opportunity to glorify God, and death becomes the gateway to eternal life with Him.